Convergence Research Directions in Cognitive Sensor Networks for Elderly Housing Design - Shinil Suh; Byung-Seo Kim; Jae Hee Chung (International Journal of Distributed Sensor Networks)
As part of resolving the issue related to super-aging society, various information systems for the elderly care have been developed utilizing cognitive sensor networks. However, many sensor network-based systems cognizing radios, resources, environments, and so forth are not practically feasible and useful for the elderly themselves. Therefore, this paper tries to propose novel research directions for designing smart residential environment for the elderly in terms of converging information technologies including cognitive sensor networks and architectural design. In this paper, we clarify the definition of smart home from the literatures and briefly surveys cognitive sensor network-based systems for smart elderly housing. After that, this paper proposes research directions for cognitive wireless sensor networks not only for the elderly smart home services, but also for cooperating with architecture technologies. The proposed directions are to utilize cognitive radio technologies, to classify sensor network technologies according to the types of the elderly, to expand sensor networks services for the elderly housing to the wider area such as blocking unnecessary energy loss, to embed sensor network modules into BIM system, and to research sensor networks fit to modular construction.